2008
DOI: 10.1093/rpd/ncn042
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance testing and QA of interventional cardiology systems

Abstract: Interventional cardiology (IC) is a rapidly growing field of medical specialisation. Such procedures are complex and may subject patients and operators to higher levels of risk than those encountered in general radiology. Acceptance testing and quality assurance (QA) of radiological equipment, including IC equipment, is a requirement of the EU Medical Exposures Directive (MED) (97/43/EURATOM). In addition, the MED identifies interventional radiology as an area of special concern. This study presents the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) indicated that one of the main sources of artificial radiation to the world population is interventional cardiology (IC) (UNSCEAR 2008(UNSCEAR , 2013. Such procedures are complex and may involve prolonged irradiation, subjecting patients and operators to higher radiation doses than those encountered in general radiology (Dowling et al 2008). Particular attention should be paid to the radiation doses received by paediatric patients as they are more sensitive to radiation (Bacher et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) indicated that one of the main sources of artificial radiation to the world population is interventional cardiology (IC) (UNSCEAR 2008(UNSCEAR , 2013. Such procedures are complex and may involve prolonged irradiation, subjecting patients and operators to higher radiation doses than those encountered in general radiology (Dowling et al 2008). Particular attention should be paid to the radiation doses received by paediatric patients as they are more sensitive to radiation (Bacher et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The dosimeters used in this experiment were the nanoDot optically stimulated luminescence (OSL) dosimeters and InLight TM MicroStar reader manufactured by Landauer, Inc., USA (Glenwood, IL, USA). The nanoDot OSL dosimeter was made of 5 mm diameter and 0.2 mm-thick plastic disks infused with Al 2 O 3 :C. The disks are encased in 10 × 10 × 2 mm 3 light-tight plastic holders with a density of 1.03 g/cm 3 . Prior to the radiation dose measurements, the OSLDs were calibrated to minimize measurement errors.…”
Section: Osldsmentioning
confidence: 99%
“…2 mm 3 light-tight plastic holders with a density of 1.03 g/cm 3 . Prior to the radiation dose measurements, the OSLDs were calibrated to minimize measurement errors.…”
Section: Osldsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 de la OIEA (IAEA, 2008) los valores recopilados de tasa de kerma en la superficie de un paciente estándar de 20 cm de PMMA son los siguientes: para modos de fluoroscopia bajos entre 10 -28 mGy/min, medios entre 10 -52 mGy/min y altos entre 32 -120 mGy/min. Además, Dowling (Dowling et al, 2008) obtiene valores entre 3 y 25 mGy/min en equipos de cardiología intervencionista. Haciendo un comparación con los valores de tasa de kerma en la superficie del paciente (20 cm de espesor) determinados en este estudio, los modos de fluoroscopia se encuentran en un rango de 5 a 23 mGy/min sin magnificación y en un rango de 9 a 56 mGy/min cuando se utiliza una magnificación de 22 cm.…”
Section: Procedimientos Diagnósticos Procedimientos Terapéuticosunclassified